2021
DOI: 10.1108/ejtd-06-2021-0071
|View full text |Cite
|
Sign up to set email alerts
|

Contextual antecedents of job crafting: review and future research agenda

Abstract: Purpose The purpose of this study is to critically review current studies on job crafting to identify contextual factors related to employees’ job crafting and to integrate the findings to help organizations improve employees’ job crafting. Design/methodology/approach Based on the guidelines provided by Torraco (2016), the authors reviewed 44 quantitative studies on job crafting published between 2001and 2020. Findings The authors identified 35 contextual antecedents of job crafting at the job (11), group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 83 publications
0
26
0
2
Order By: Relevance
“…JC refers to changes that staff members launch in the level of job demands and job resources to make their own jobs more meaningful, engaging, and satisfying (Afsar et al, 2019). As such, previous studies have demonstrated that leaders' behaviors indicating appreciation for change are considered an important factor in motivating subordinates' JC (Park & Park, 2021). As TL focuses on change (Bass, 1985), it could be a useful antecedent to JC (Wang et al, 2017).…”
Section: Transformational Leadership and Job Craftingmentioning
confidence: 99%
See 4 more Smart Citations
“…JC refers to changes that staff members launch in the level of job demands and job resources to make their own jobs more meaningful, engaging, and satisfying (Afsar et al, 2019). As such, previous studies have demonstrated that leaders' behaviors indicating appreciation for change are considered an important factor in motivating subordinates' JC (Park & Park, 2021). As TL focuses on change (Bass, 1985), it could be a useful antecedent to JC (Wang et al, 2017).…”
Section: Transformational Leadership and Job Craftingmentioning
confidence: 99%
“…Despite the importance of JC, the majority of previous studies have focused on examining the consequences of crafting behaviors and a limited number of researches have examined the predictors (Kiliç et al, 2020). Recently, Park and Park (2021) divided contextual antecedents of JC into four categories: organizational characteristics, leadership, group and job characteristics. According to earlier studies leaders may have a considerable impact on the opportunity for subordinates to engage in JC behaviors (Park & Park, 2021).…”
Section: -Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations